2014
DOI: 10.1038/sc.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Does consumption of polyunsaturated fatty acids influence on neurorehabilitation in traumatic spinal cord-injured individuals? a double-blinded clinical trial

Abstract: Study design: A double-blinded randomized clinical trial. Objectives: The anti-inflammatory and neuroprotective effect of omega-3 fatty acids have been shown so far, but still its influence on clinical measures in spinal cord-injured human models were not known. We tried to investigate changes in disability and dependency scores in chronic traumatic spinal cord-injured patients after 14 months of o-3 fatty-acid consumption. Methods: Main inclusion criteria were: traumatic spinal cord injury (SCI) and post inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…46 Here, we found that the cytoskeleton of spinal MNs in mice was significantly damaged after SCI, and further analysis revealed that the cytoskeletal protein expression was These results suggested the significance of DHA in the survival of posterior spinal MNs after SCI, which was consistent with previous findings. 25,26 Furthermore, our results showed that DHA has a positive effect on the cytoskeleton of spinal MNs after SCI. Studies have shown that the signaling pathway of axon regeneration after injury is focused on the regulation of cytoskeletal dynamics.…”
Section: ■ Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…46 Here, we found that the cytoskeleton of spinal MNs in mice was significantly damaged after SCI, and further analysis revealed that the cytoskeletal protein expression was These results suggested the significance of DHA in the survival of posterior spinal MNs after SCI, which was consistent with previous findings. 25,26 Furthermore, our results showed that DHA has a positive effect on the cytoskeleton of spinal MNs after SCI. Studies have shown that the signaling pathway of axon regeneration after injury is focused on the regulation of cytoskeletal dynamics.…”
Section: ■ Discussionmentioning
confidence: 51%
“…In recent years, research on docosahexaenoic acid (DHA) and its significance to bodily health and disease risk have been increasingly in-depth, and its role in the prevention and treatment of neurological diseases has also received extensive attention. , Some studies demonstrated that DHA has beneficial effects on SCI, , including inhibiting inflammation, , protecting nerve cells and activating their regenerative process, promoting the expression of neuroprotective genes and antiapoptosis, and alleviating neuropathic pain. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth cone is the end of the neuronal axon, which plays an important role in the growth of nerve cells (5). Therefore, the study of the growth cone can provide good observation of the effects of some external stimuli or external substances on the development of nerve tissue (7).…”
Section: Original Articlementioning
confidence: 99%
“…In recent years, PUFAs were recommended to treat systemic pathological conditions, [ 18 ] and administration of omega-3 PUFAs has been proposed for the treatment neurological diseases such as hyperactive disorder, attention deficit, [ 19 ] Alzheimer, [ 20 ] depression, [ 21 ] neurodegenerative diseases, [ 22 ] and spinal cord injury. [ 23 ] These FAs mediate numerous physiological functions and have therapeutic potential for neuro-traumatic conditions [ 24 ] and omega-3 FAs intake provide relief from neuropathic pain caused by diabetic neuropathy. [ 25 ] In addition, patients affected by cervical radiculopathy and thoracic outlet syndrome reported long term significant pain attenuation with high oral doses of omega-3 FAs.…”
Section: Introductionmentioning
confidence: 99%